Micromachining Characterization of Ultrathin Ni-membranes - Mahawar, Vijay; Singh, Kundan Kumar; Singh, Ramesh (9th International Conference on MicroManufacturing (ICOMM 2014), 2014)
Thin membranes of different materials find extensive use in fabrication of Micro Electro Mechanical Systems (MEMS) devices.Machined membranes are used as heat sinks by fabricating micro channels for high heat transfer rates in micro heat exchanger and as membrane stacks of Proton Exchange Membrane fuel cells. These membranes can also be used as masks for lithography for creating features on silicon wafers for semiconductor industry. Due to low flexural rigidity of the ultra-thin membranes, fixturing of membranes poses additional challenges. The plastic deformation induced during machining and the burr formation/tearing needs to be minimized for improving the geometrical accuracy of the machined feature. The cutting forces in membrane machining are very small in magnitude and an accurate model for the prediction of these forces needs to be developed and validated. The current study focuses on micromilling of ultrathin membranes. A parametric study of micromilling parameters has been conducted to characterize the geometrical accuracy of machined micro slots on two workpieces, ultra-thin (20 ?m) pure Ni membranes and relatively thick (200 ?m) pure Ni workpiece. A mechanistic model for cutting forces has been developed for thin membranes to predict forces involved and has been validated with the experimental data. Scanning electron microscopy (SEM), white light interferometer (WLI) and optical microscope were used for characterization of dimensional accuracy of micro slots geometry in terms of their width. The minimum geometrical accuracies error obtained were 50% and 19% for 100?m and 400?m tools respectively for 20?m thin Ni membrane and 7% for 200?m thick Ni workpiece using 400?m tool. Cutting forces are measured using a three directional Kristler dynamometer (Minidyne 9256 C2) for both the thickness of workpieces. The maximum resultant cutting forces of X and Y directions were 1.3 N at the feed rate of 10um/flute and 60000 RPM for 20?m thin Ni membrane which is quite low as compared to thick materials.
Keywords: cutting coefficients; high speed micromilling; force modelling; flexural rigidity; scanning electron microscopy; overall slot width; thin membranes; white light interferometer